Pengaruh Pengendalian Intern Terhadap Penatausahaan Aset Tetap Serta Implikasinya Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Iasha Nastitie Auliawati Rachma, - (2020)
This study aims to determine the effect of internal control on fixed asset administration; the effect of fixed asset administration on the quality of financial reports; the effect of internal control on the quality of financial reports; as well as the effect of internal control on the quality of financial reports through the administration of fixed assets. The research method used in this research is descriptive method and causality with a quantitative approach. The population in this study were 73 SKPDs located within the Bandung City Government. The sampling method in this study used the Simple Random Sampling technique which is expected that each population has the same opportunity to become a sample, so that the selected sample can represent all existing sub-populations. The data used are primary data with a questionnaire technique. Hypothesis testing in this study uses path analysis with SPSS software tools. The results of hypothesis testing show that (1) internal control has a positive effect on fixed asset administration, which means that the better internal control is, the better the administration of fixed assets; (2) fixed asset administration has a positive effect on the quality of financial reports, which means that the better the administration of fixed assets, the better the quality of the financial statements; (3) internal control has a positive effect on the quality of financial reports, which means that the better the internal control, the better the quality of the financial reports; (4) internal control has a positive effect on the quality of financial reports by mediating the administration of fixed assets, which means that if there is good control over the administration of fixed assets / regional property, the better the quality of financial reports in the City Government of Bandung